2021
DOI: 10.12688/openreseurope.13313.1
|View full text |Cite
|
Sign up to set email alerts
|

A case study research on interoperability improvement in Smart Grids: state-of-the-art and further opportunities

Abstract: With the topic of Smart Grids taking up momentum, challenges to integrate systems from various vendors’ at large scale in a critical infrastructure have arisen. This issue is usually tackled utilizing standards and, therefore, agreements between the various parties. However, the aspect of the interoperability between systems is not only defined by physical connections, but has a multi-faceted dimension which needs to be dealt with at all layers in order for a semantic and cost-efficient integration. Within thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Note that the benefits of interoperability profiling and testing have also been recognised in the energy sector (Gopstein et al, 2021;Schütz et al, 2021;SGCG, 2012aSGCG, , 2012b) and related methods have been researched and demonstrated (Gottschalk et al, 2018;Papaioannou et al, 2018).…”
Section: Solutions That Are Only Applied In Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the benefits of interoperability profiling and testing have also been recognised in the energy sector (Gopstein et al, 2021;Schütz et al, 2021;SGCG, 2012aSGCG, , 2012b) and related methods have been researched and demonstrated (Gottschalk et al, 2018;Papaioannou et al, 2018).…”
Section: Solutions That Are Only Applied In Individualmentioning
confidence: 99%
“…The experiences in these sectors have been documented by several authors, whom we refer to in this paper. For the electricity sector, we rely on Schütz et al (2021), who compare different methods for achieving interoperability in the energy sector, Gopstein et al (2021), who focus on smart grid interoperability standards, and Papaioannou et al (2018), who developed a method for interoperability profiling and testing. For the public administration sector, we refer to Wimmer et al (2018), who review interoperability governance models at the EU and national levels in the public administration and healthcare sectors, and Gottschalk (2009), who proposes a maturity model for interoperability in digital government.…”
Section: Introduction *mentioning
confidence: 99%
“…Due to the challenging integration of renewable energy resources from heterogeneous stakeholders into the power system, the GridWise Architecture Council (GWAC), a team of people from industry and academia from sectors such as energy, IT, or security, developed guiding principles and architectures for intelligent energy systems [32]. The GWAC not only explains the technical and informational interfaces of different actors and their systems, in particular, their interoperability but also highlights the importance of organizational alignment between them [7,33,34].…”
Section: Basic Modelling In Sgammentioning
confidence: 99%
“…Finally, the Organisational level entails interoperability on a political level, which means that the stakeholders have the same economic and, regulatory framework as well as the business procedures and objectives. The GWAC stack shows that the interoperability levels start at the bottom with a simple technical connection, and end at the top level with organizational and regulatory agreements to establish plug-and-play between the systems [33].…”
Section: Basic Modelling In Sgammentioning
confidence: 99%
“…The experiences in these sectors have been documented by several authors, whom we refer to in this paper. For the electricity sector, we rely on Schütz et al (2021), who compare different methods for achieving interoperability in the energy sector, Gopstein et al (2021), who focus on smart grid interoperability standards, and Papaioannou et al (2018), who developed a method for interoperability profiling and testing. For the public administration sector, we refer to Wimmer et al (2018), who review interoperability governance models at the EU and national levels in the public administration and healthcare sectors, and Gottschalk (2009), who proposes a maturity model for interoperability in digital government.…”
Section: Introduction *mentioning
confidence: 99%